Analisis Kelayakan Usaha Industri Kecil Sandal (Studi Kasus di Kelurahan Prajurit Kulon, Kecamatan Prajurit Kulon, Kota Mojokerto) - Tri Agus Kusuma Wardana Ashari Putra; Arga Christian Sitohang (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to analyze the level of financial feasibility of small industrial sandal businesses in Prajurit Kulon Village, Prajurit Kulon District, Mojokerto City. Which aims to determine and analyze the cost, revenue, business profits and analyze the feasibility of the business financially, in this study the analysis used Revenue Cost Ratio (R / C ratio), Benefit Cost Ratio (B / C ratio) and ROI (Return On Investment) so that it can be known whether the sandal business is feasible or not to run. This research took as many as 6 informants who will provide information through interviews. The results of this study indicate that after reviewing the financial aspects that the 6 sandal businesses namely Mr. Taufik, Mr. Annas, Mr. Oky, Mr. Marno, Mr. Wawan and Mr. Rudi are feasible to run.